Identification of source and sink populations for the emergence and global spread of the East-Asia clone of community-associated MRSA. Issue 1 (December 2016) - Ward, Melissa; Goncheva, Mariya; Richardson, Emily; McAdam, Paul; Raftis, Emma; Kearns, Angela; Daum, Robert; David, Michael; Lauderdale, Tsai; Edwards, Giles; Nimmo, Graeme; Coombs, Geoffrey; et al.
Abstract Background Our understanding of the factors influencing the emergence, dissemination and global distribution of epidemic clones of bacteria is limited. ST59 is a major epidemic clone of community-associated MRSA in East Asia, responsible for extensive morbidity and mortality, but has a much lower prevalence in other parts of the world. The geographic origin of ST59 and its international routes of dissemination are unclear and disputed in the literature. Results To investigate the origin and spread of the ST59 clone, we obtained whole genome sequences of isolates from four continents, sampled over more than a decade, and carried out a time-scaled phylogeographic analysis. We discover that two distinct ST59 clades emerged concurrently, in East Asia and the USA, but underwent clonal expansion at different times. The East Asia clade was strongly enriched for gene determinants associated with antibiotic resistance, consistent with regional differences in antibiotic usage. Both clones spread independently to Australia and Europe, and we found evidence of the persistence of multi-drug resistance following export from East Asia. Direct transfer of strains between Taiwan and the USA was not observed in either direction, consistent with geographic niche exclusion. Conclusions Our results resolve a longstanding controversy regarding the origin of the ST59 clone, revealing the major global source and sink populations and routes for the spread of multi-drug resistant clones. Additionally, our findings indicate that diversification of the accessory genome of epidemic clones partly reflects region-specific patterns of antibiotic usage, which may influence bacterial fitness after transmission to different geographic locations.